2020
DOI: 10.1002/cam4.3496
|View full text |Cite
|
Sign up to set email alerts
|

Computer‐based simulation to reduce EHR‐related chemotherapy ordering errors

Abstract: Background The electronic health record (EHR) is a contributor to serious patient harm occurring within a sociotechnical system. Chemotherapy ordering is a high‐risk task due to the complex nature of ordering workflows and potential detrimental effects if wrong chemotherapeutic doses are administered. Many chemotherapy ordering errors cannot be mitigated through systems‐based changes due to the limited extent to which individual institutions are able to customize proprietary EHR software. We hypot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The twelve articles did not demonstrate the inclusion of patients, they involved the development of some teaching resource or creation of resources to reduce and prevent adverse drug events through simulation methods. Of these articles, 01 involved the creation of a freeze-dried ampoule of Dantrolene (Giraldo-Gutiérrez et al, 2018); 01 identified unreported errors (You et al, 2015); 02 studies developed drug labels for simulations (Dollinger et al, 2016;GARCIA, et al, 2017); 01 alert created in simulations, 2017); 01 created alerts in medication prescription software to avoid errors (RUSS et al, 2014); 01 used simulated software to verify medication orders and reconciliation by pharmacists (Metzger et al, 2015); 01 involved creating software to train on security vulnerabilities in chemotherapy orders (Wyatt et al, 2020); 01 created a gamification simulator for preparing medicines (Booth et al, 2018); 01 creation of a device for the infusion of intravenous medications after checking the barcode (Khan et al, 2016); an integrative review that shows that high and low fidelity simulations contribute to knowledge acquisition (Santana et al, 2020); one study compared the frequency of errors after safety simulation training (JONES et al, 2021); one developed a simulated electronic medication administration system (Booth et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The twelve articles did not demonstrate the inclusion of patients, they involved the development of some teaching resource or creation of resources to reduce and prevent adverse drug events through simulation methods. Of these articles, 01 involved the creation of a freeze-dried ampoule of Dantrolene (Giraldo-Gutiérrez et al, 2018); 01 identified unreported errors (You et al, 2015); 02 studies developed drug labels for simulations (Dollinger et al, 2016;GARCIA, et al, 2017); 01 alert created in simulations, 2017); 01 created alerts in medication prescription software to avoid errors (RUSS et al, 2014); 01 used simulated software to verify medication orders and reconciliation by pharmacists (Metzger et al, 2015); 01 involved creating software to train on security vulnerabilities in chemotherapy orders (Wyatt et al, 2020); 01 created a gamification simulator for preparing medicines (Booth et al, 2018); 01 creation of a device for the infusion of intravenous medications after checking the barcode (Khan et al, 2016); an integrative review that shows that high and low fidelity simulations contribute to knowledge acquisition (Santana et al, 2020); one study compared the frequency of errors after safety simulation training (JONES et al, 2021); one developed a simulated electronic medication administration system (Booth et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The most frequent simulations are performed in high-fidelity laboratories (58%), using mannequins, labels, equipment and an environment prepared to get as close as possible to real care (Minor et al, 2019;Lane;Roberts, 2021;Kothari et al, 2021;O' Leary et al, 2013;Damhoff et al, 2014;Hayes et al, 2015;Keating et al, 2021;Raurell-Torredà et al, 2021;Russ et al, 2014;Hawley et al, 2019;Dudas;Barone, 2015;Stevens et al, 2015;Wyatt et al, 2020;Siebert et al, 2021;Adapa et al, 2012;booth et al, 2018;Breitkreuz et al, 2016;Estock et al, 2018;Enriquez et al, 2017;Prakash et al, 2014;Pinkney et al, 2014;VYAS et al, 2012;MERRY et al, 2017;GARCIA et al 2017;Metzger et al, 2015;Khan et al, 2016;Cooke et al, 2017;Pinkney et al, 2019;Frenzel et al, 2020;Hebbar et al, 2018;Cotteret et al, 2019;Porter et al, 2014;Wang et al, 2017;Booth et al, 2017;Lobos et al, 2019;Thibault et al, 2019;Crimmins et al, 2018;Berg et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation